Plastic bending : theory and applications - Yu, T. X. (Tongxi X.), 1941- (Series on engineering mechanics, 1996)
From the point of view of mechanics, this monograph systematically demonstrates the theory of plastic bending and its engineering applications; most of the contents of the book are based on the authors' research in the past decade. The monograph not only expounds the contributions of the authors to the fundamental theory of plastic bending, but also presents various applications of the theory in sheet metal forming, particularly in the analysis and prediction of springback and wrinkling of strips and plates subjected to bending or stamping. In addition to theoretical modelling, attention has also been paid to the development of related numerical methods; comparisons with experimental results are also presented.